2009
DOI: 10.1016/j.nbd.2008.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Bdnf overexpression in hippocampal neurons prevents dendritic atrophy caused by Rett-associated MECP2 mutations

Abstract: The expression of the methylated DNA-binding protein MeCP2 increases during neuronal development, which suggests that this epigenetic factor is crucial for neuronal terminal differentiation. We evaluated dendritic and axonal development in embryonic day-18 hippocampal neurons in culture by measuring total length and counting branch point numbers at 4 days in vitro, well before synapse formation. Pyramidal neurons transfected with a plasmid encoding a small hairpin RNA (shRNA) to knockdown endogenous Mecp2 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 102 publications
6
86
1
1
Order By: Relevance
“…MeCP2 mutant mice have reduced BDNF levels. This reduction, and the neuronal atrophy characteristic of RTT, can be reversed by forebrain-specific overexpression of Bdnf in vivo (46), an effect that was recently confirmed in cultured hippocampal neurons (180). In addition to Bdnf, a recent study identified seven other genes as direct binding targets of MeCP2 in the mouse brain (346), including myelin-associated proteins and dopamine decarboxylase.…”
Section: B Rett Syndromementioning
confidence: 80%
See 1 more Smart Citation
“…MeCP2 mutant mice have reduced BDNF levels. This reduction, and the neuronal atrophy characteristic of RTT, can be reversed by forebrain-specific overexpression of Bdnf in vivo (46), an effect that was recently confirmed in cultured hippocampal neurons (180). In addition to Bdnf, a recent study identified seven other genes as direct binding targets of MeCP2 in the mouse brain (346), including myelin-associated proteins and dopamine decarboxylase.…”
Section: B Rett Syndromementioning
confidence: 80%
“…At the anatomical level, significant reductions in both gray and white matter are observed at the regressive stage (249). At the cellular level, neurons in RTT patients may have a reduced density of dendritic spines (180), and murine RTT models display axonal and dendritic spine abnormalities (20). Moreover, mouse models of RTT exhibit an overall decrease in exploratory activity (49,127), show severe cognitive deficits, and have impaired synaptic plasticity (61).…”
Section: B Rett Syndromementioning
confidence: 99%
“…For example, ethanol exposure (Reiter-Funk and Dohrman, 2005;Roivainen et al, 1995a;Zou et al, 1993) and MeCP2 overexpression (Larimore et al, 2009;Rastegar et al, 2009) have been shown to show similar patterns of increased neurite branching. However, ethanol exposure has also been shown to reduce the neurite outgrowth (Camarillo and Miranda, 2008), similar to few studies on MeCP2-deficiency (Nguyen et al, 2012;Rastegar et al, 2009;Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, conditional overexpression of BDNF in excitatory forebrain neurons of Mecp2-deficient mice-achieved by crossing BDNF STOP mice with Mecp2;cre mice-led to the improvement of some of their RTT-like neurologic phenotypes [81]. In addition, in vitro expression of green fluorescent prot ein-tagged BDNF from a cytomegalovirus-driven plasmid rescued the dendritic atrophy caused by short hairpin RNA-mediated knockdown of Mecp2 in cultured rat hippocampal neurons [82], and the dendritic atrophy and lower spine density in cultured hippocampal neurons from Mecp2 knockout mice (Xu and LP-M, in preparation). Unfortunately, BDNF has very low BBB permeability, which limits the bioavailability of peripherally administered BDNF as a potential therapy.…”
Section: Neurotrophins and Growth Factors: Brain-derived Neurotrophicmentioning
confidence: 99%